Exemplary and Unacceptable Workplace Communication Skills. Issue 4 (December 2020) - Coffelt, Tina A.; Smith, Frances L. M.
Thematic analysis of interviews with 22 managers highlight their perspectives on exemplary and unacceptable workplace communication skills. Exemplary skills were perceived to be relatability, documentation, and audience awareness/adaptation, while unacceptable skills were verbal aggression, deception, and defensive communication behaviors. The findings contribute to closing-the-gap research by identifying highly notable skills—both positive and negative—on typical lists of business and professional communication skills. This study also enriches anticipatory socialization scholarship by its application to vocational preparation. Business and professional communication instructors can use the findings here when deciding what topics to emphasize in a course.